"It's Humanity, Stupid!": Values and the Definition of Public Goods. Issue 2 (3rd April 2021) - Davis, Ann E.
Abstract: The COVID-19 pandemic represents a major threat to the economy and an opportunity for transformation. This article suggests that the importance of the human role of the economy is now unusually palpable, and calls into question the divisions and inequalities across spatial and institutional specialization. We propose a new category of "public good" to account for the importance of political participation in the design of human institutions, to refer to both recognition and security. Rather than simply the opposite of private goods, the concept of public goods can incorporate human capacity and public agency. Whereas typical economic categories are presumably "technical, " without relationship to humans, these new proposed categories highlight the importance of humans, and humanity, as the primary focus of economic "performance, " not only in productivity and efficiency but also in quality of life and work.